2019
DOI: 10.1007/978-3-030-29390-1_10
|View full text |Cite
|
Sign up to set email alerts
|

As Light as Your Scent: Effects of Smell and Sound on Body Image Perception

Abstract: How people mentally represent their body appearance (i.e., body image perception-BIP) does not always match their actual body. BIP distortions can lead to a detriment in physical and emotional health. Recent works in HCI have shown that technology can be used to change people's BIP through visual, tactile, proprioceptive, and auditory stimulation. This paper investigates, for the first time, the effect of olfactory stimuli, by looking at a possible enhancement of a known auditory effect on BIP. We present two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 57 publications
5
32
0
Order By: Relevance
“…Previous studies have mostly used senses that can easily be mapped spatially, such as vision, touch, and proprioception to induce illusory embodiment. Other, less primarily spatial senses like olfaction have largely been neglected in the literature (see Brianza et al., 2019, for an exception). Compared with the strength of other bodily contingencies (e.g., visuo-tactile), scents may be a mild cue to elicit illusory embodiment.…”
mentioning
confidence: 99%
“…Previous studies have mostly used senses that can easily be mapped spatially, such as vision, touch, and proprioception to induce illusory embodiment. Other, less primarily spatial senses like olfaction have largely been neglected in the literature (see Brianza et al., 2019, for an exception). Compared with the strength of other bodily contingencies (e.g., visuo-tactile), scents may be a mild cue to elicit illusory embodiment.…”
mentioning
confidence: 99%
“…We are seeing initial efforts, sometimes from an artistic design perspective, to explore smell-based emotionally responsive wearable technology. For example, smell has been shown to influence how we feel about ourselves ( Tillotson, 2017 ; Amores et al, 2018 ), affect our body image perception (BIP) ( Brianza et al, 2019 ) and support sleep and dreaming ( Carr et al, 2020 ). More opportunities around smell can be studied with respect to human sensory perception and integration due to these ongoing technological advances.…”
Section: Expanding Multisensory Integration: Current Tools/methods and Emerging Technologymentioning
confidence: 99%
“…BIP refers to "perceptions, attitudes and beliefs pertaining to one's own body" [49], comprising emotional attitudes towards it. For instance, Brianza et al, [16] found that lemon scent is significantly associated with a thin body while vanilla with a thick body. They also showed subjective reports of feeling lighter when smelling lemon and heavier when smelling vanilla.…”
Section: Effect Of Smell On Emotionsmentioning
confidence: 99%